2020
DOI: 10.3390/nu12071997
|View full text |Cite
|
Sign up to set email alerts
|

Are the Results of a Combined Behavioural and Surgical Treatment of Morbid Obesity Satisfactory and Predictable?

Abstract: Treatment of subjects with morbid obesity (Body Mass Index (BMI) > 40 kg/m2 or > 35 kg/m2 with obesity-related complications) often fails. This study explored the biopsychosocial predictors of dropout and weight loss during a combined behavioural and surgical weight-reduction program. Behavioural treatment for six months was followed by bariatric surgery and a visit six months after surgery. The success criterion was the loss of ≥50% of excess BMI above 25 kg/m2 (%EBMIL). Thirty-one men and 113 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Moreover, our results showed that a low white blood cell count is one of the risk factors for perioperative fever, whereas Munro et al indicated that routine preoperative measurement showed that the platelet count was abnormally low in less than 1.1% of patients, and that platelet count results rarely, if ever, lead to a change in patient management [ 43 ]. In addition, since housemates have been reported to be a predictor of successful surgical treatment for morbid obesity, there is a slight suggestion that the presence of housemates may have an effect on the patient’s BMI prior to surgery and secondarily on complication prevention [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our results showed that a low white blood cell count is one of the risk factors for perioperative fever, whereas Munro et al indicated that routine preoperative measurement showed that the platelet count was abnormally low in less than 1.1% of patients, and that platelet count results rarely, if ever, lead to a change in patient management [ 43 ]. In addition, since housemates have been reported to be a predictor of successful surgical treatment for morbid obesity, there is a slight suggestion that the presence of housemates may have an effect on the patient’s BMI prior to surgery and secondarily on complication prevention [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the prospective cohort study MO-BiPS (Morbid Obesity—Bio-Psycho-Social disorders) were used 8 . Blood samples from a biobank were analysed and used in this retrospective cohort study.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…The study used data from the prospective cohort study "Morbid Obesity -Bio-Psycho-Social impacts" (MO-BiPS) (Farup, 2020). The subject characteristics and the POPs and hormone analyses have been published in different contexts in two papers, one studied the levels of POPs after bariatric surgery, and the other APOE polymorphism and endocrine functions (Jansen et al, 2018;Farup et al, 2022).…”
Section: Methodsmentioning
confidence: 99%